Organizational Lerning and Strategy: Information Processing Approach of Organizaitonal Learning to Perform Strategic Choice Analysis - Agustian Budi Prasetya (Bina Nusantara University, 2017)
Study of organizational learning required to discuss the issue of strategy to understand company’s organizational knowledge and how company applied the organizational knowledge toward the changing of the environment. Method of the analysis for this research was based on desk research thoroughly on the existing literature. This research analyzed the viewpoints of different researchers in organizational learning and elaborates the information processing abilities approach of Organizational Learning (OL). Based on desk research on literature, the research discussed information processing approach to explain organizational learning and strategy choice by describing the importance of information and assumptions, the activities of knowledge acquisition, interpreting and distribution of the knowledge, typology of exploitation and exploration learning. It proposed the importance of the company to perform alignment between internal managerial process arrangement and external environment while doing the learning, based on the strategic choice space, as theatrical clustering map of the learning, the fit, the alignment, and the alliances of the organization. This research finds that the strategic space might help the analysis of balancing between exploitation and exploration learning while applying the analysis of varied firm characteristics, strategic orientation, and industrial environments.